Association of manganese superoxide dismutase gene polymorphism (Ala-9Val) and breast cancer in males and females Associação do polimorfismo do gene da superóxido dismutase dependente de manganês (Ala-9Val) em homens e mulheres com câncer de mama - Claudia Giuliano Bica; Ivana Beatrice Mânica da Cruz; Leonardo Leiria de Moura da Silva; Nadima Vieira Toscani; Cláudio Galleano Zettler; Márcia Silveira Graudenz (Sociedade Brasileira de Patologia Clínica, 2007)
INTRODUCTION: One of the several metabolic pathways involved in breast carcinogenesis is the human polymorphism in the mitochondrial targeting sequence Ala-9Val of the manganese superoxide dismutase (MnSOD) gene, which has been previously associated with increased risk of breast cancer in females. Since there is no previous report on this polymorphism in male breast cancer, the objective of this study is to analyze MnSOD polymorphism in a population of males and females with breast cancer from the southernmost state of Brazil, compared to healthy controls. METHODS: A case-control study of one hundred patients affected by breast cancer (11 men and 89 women) and 370 healthy age-adjusted database controls was performed. DNA was extracted from paraffin-embedded tumoral tissue. MnSOD polymorphism was determined by PCR-RFLP techniques using restriction enzyme Hae III. Chi-square test was used to compare MnSOD frequency distribution. RESULTS: MnSOD genotypic frequencies in all patients with breast cancer were AA = 15%; AV = 56%; VV = 29% and controls AA = 6.5%; AV = 68.1% and VV = 25.4%. Both male and female patients with breast cancer presented significantly higher AA frequencies compared to controls (p = 0.035), suggesting strong association of this genotype with breast cancer. A 2.15-fold (95% confidence interval [CI] 1.393-4.541) risk of breast cancer was found among individuals carrying the MnSOD AA allele-containing genotypes compared with the MnSOD VV and AV genotypes. DISCUSSION: These results confirm the already established association of MnSOD AA genotype with female breast cancer and further indicate a similar frequency distribution and increased risk in the male population. INTRODUÇÃO: Uma das diversas rotas metabólicas envolvidas no processo de carcinogênese da mama é o polimorfismo Ala-9Val do gene da superóxido dismutase dependente de manganês, cuja associação com o aumento do risco de câncer de mama em mulheres já é bem estabelecida na literatura. Contudo, não existem estudos envolvendo esse polimorfismo no carcinoma de mama em homens, principalmente devido à baixa prevalência dessa neoplasia. O objetivo deste estudo é analisar o polimorfismo da MnSOD em uma população de homens e mulheres com câncer de mama no sul do Brasil, comparando tais achados com controles saudáveis. MÉTODOS: Foi realizado um estudo de caso-controle em cem pacientes com câncer de mama (11 homens e 89 mulheres) e 370 controles saudáveis. O DNA foi extraído do tecido tumoral emblocado em parafina. O polimorfismo da MnSOD foi determinado por técnicas de PCR-RFLP usando a enzima de restrição Hae III. O teste do qui quadrado foi usado para comparar a distribuição das freqüências dos polimorfismos. RESULTADOS: As freqüências genotípicas dos pacientes com câncer de mama foram AA = 15%; AV = 56%; VV = 29% e dos controles AA = 6,5%; AV = 68,1% e VV = 25,4%. Os pacientes com câncer de mama, tanto as mulheres como os homens, apresentaram freqüências significativamente mais elevadas do genótipo AA quando comparadas aos controles (p = 0,035), sugerindo associação forte desse genótipo com o câncer de mama. O intervalo de confiança foi de 1,393-4,541 (95%) e o risco encontrado foi de 2,15 para indivíduos portadores do genótipo AA, quando comparados com os controles que tinham os genótipos VV e AV da MnSOD. DISCUSSÃO: Esses resultados confirmam a associação já estabelecida do genótipo da MnSOD AA com câncer de mama em mulheres e indicam distribuição de freqüência similar e risco aumentado na população masculina.